2018
DOI: 10.1177/8755122518780742
|View full text |Cite
|
Sign up to set email alerts
|

Medications and Micronutrients: Identifying Clinically Relevant Interactions and Addressing Nutritional Needs

Abstract: Prescription drug use is on the rise, and the use of dietary supplementation remains common. In the United States, more than half of all adults take a dietary supplement in any given month. As a result, drug-nutrient interactions are becoming an important consideration when pharmacists counsel patients about their drug regimens. We reviewed the literature to identify common and/or clinically relevant drug-nutrient interactions that pharmacists may encounter in practice. Data Sources: A MEDLINE search for Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…In particular, vitamin B 12 and iron (Fe) absorption may | 473 be inhibited, necessitating routine monitoring. [60][61][62] These drugs may also inhibit the absorption of vitamin C, calcium (Ca), magnesium (Mg), zinc (Zn), beta-carotene, and other nutrients; however, studies have not always been consistent or have been reported infrequently, and further studies are needed. [60][61][62] Drugs that promote GI tract motility may inhibit the absorption of vitamins and minerals.…”
Section: Effect On Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, vitamin B 12 and iron (Fe) absorption may | 473 be inhibited, necessitating routine monitoring. [60][61][62] These drugs may also inhibit the absorption of vitamin C, calcium (Ca), magnesium (Mg), zinc (Zn), beta-carotene, and other nutrients; however, studies have not always been consistent or have been reported infrequently, and further studies are needed. [60][61][62] Drugs that promote GI tract motility may inhibit the absorption of vitamins and minerals.…”
Section: Effect On Food Intakementioning
confidence: 99%
“…[60][61][62] These drugs may also inhibit the absorption of vitamin C, calcium (Ca), magnesium (Mg), zinc (Zn), beta-carotene, and other nutrients; however, studies have not always been consistent or have been reported infrequently, and further studies are needed. [60][61][62] Drugs that promote GI tract motility may inhibit the absorption of vitamins and minerals. Reportedly, stimulant laxatives may inhibit the absorption of vitamins and minerals.…”
Section: Effect On Food Intakementioning
confidence: 99%
“…The effect of combined diuretics and SGLT2i use on trace element concentration, as well as the potential interplay between SGLT2i and commonly prescribed (non‐) cardiovascular medications known to affect absorption and bioavailability of certain micronutrients (i.e. acid‐suppressing drugs, antibiotics, statins), is yet to be assessed 8 …”
Section: Factor Total Cohort (N = 79) Empagliflozin (N = 40) Placebo ...mentioning
confidence: 99%
“…acid-suppressing drugs, antibiotics, statins), is yet to be assessed. 8 In this post-hoc analysis of the EMPA-RESPONSE-AHF trial, we investigated the effect of empagliflozin on a wide array of plasma trace element concentrations. While pharmacodynamic properties may differ between medicines in the SGLT2i class, our results suggest safe trace element equilibrium with use of empagliflozin.…”
mentioning
confidence: 99%
“…One of the limitations of this study is that other factors, including exercise, supplements, medicine usage, dietary patterns, and psychological factors which have been reported to be associated with vitamin levels or the menstrual cycle, [46][47][48][49][50] were not considered and should be fully evaluated in future research. Menstrual characteristics were obtained using questionnaires, which could lead to inaccurate estimation and induce recall bias.…”
Section: Papermentioning
confidence: 99%